Coordination-bond-driven fabrication of crack-free photonic crystals. Issue 30 (21st June 2016) - Shi, X. D.; Liu, W. Y.; Zhao, D.; Li, X. T.; Dou, R. M.; Shea, K. J.; Lu, X. H.
Abstract : Centimeter-scale crack-free opal PC films are prepared in which the latex spheres are bound together through coordination bonds. Abstract : The self-assembled fabrication of large-area opal photonic crystals (PCs) that are free of cracks has remained a challenge which greatly limits the practicality of such a structure in optical and electronic applications. We report a new route in this paper for fabricating centimeter scale crack-free opal PC films in which the latex spheres are bound together through coordination bonds. The elimination of cracks in the PCs is attributed to the formation of metal ion–polymer latex spheres coordination complexes which is confirmed by shifts of the binding energy of the metal ion after the reaction. The coordination bonds enhance the interactions between the polymer latex spheres, which can neutralize the adhesion stress caused by the substrate and tension stress caused by the shrinkage of the latex spheres during the evaporation of solvent. The as-prepared PC films show a uniform diffraction color and excellent reflection properties, which proves that the formation of coordination bonds does not weaken the contrasts of the refractive index or the optical quality of the PCs. This facile fabrication of large area, crack-free opal PCs will offer significant insight into the preparation and applications of PCs in optical devices.